2004
DOI: 10.1111/j.1447-0756.2003.00166.x
|View full text |Cite
|
Sign up to set email alerts
|

Premature luteinization defined as progesterone estradiol ratio >1 on hCG administration day seems to adversely affect clinical outcome in long gonadotropin‐releasing hormone agonist cycles

Abstract: Premature luteinization, defined as P/E2 > 1 on human chorionic gonadotropin administration day, in long gonadotropin-releasing hormone agonist cycles seems to adversely affect clinical outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
23
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 17 publications
4
23
0
3
Order By: Relevance
“…In this study, FSH levels during ovarian hyperstimulation were not higher in Group 3 patients. Their elevated P 4 /E 2 (O1) still suggests an increased risk for premature luteinization (Ozcakir et al 2004).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In this study, FSH levels during ovarian hyperstimulation were not higher in Group 3 patients. Their elevated P 4 /E 2 (O1) still suggests an increased risk for premature luteinization (Ozcakir et al 2004).…”
Section: Discussionmentioning
confidence: 98%
“…The P 4 /E 2 was significantly higher in Group 3, while there was no significant difference between Groups 1 and 2. An elevated P 4 /E 2 is a well known marker of premature luteinization (Ozcakir et al 2004) and, therefore, suggested that older patients might be at higher risk for premature luteinization than the other two groups.…”
Section: Patient Populations and Cycle Characteristicsmentioning
confidence: 99%
“…However, despite pituitary down-regulation, several researchers have described a phenomenon reported as premature luteinization (PL) (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). It has been described as a subtle premature increase in serum progesterone (P) levels on the day of hCG administration above a threshold level, which varied among different studies and was usually arbitrarily defined (3)(4)(5)(6)(7).…”
mentioning
confidence: 96%
“…Another approach for explaining the influence of the P:E 2 ratio on the absence of implantation sites in hyperstimulated animals could arise from recent work by Ozcakir et al (2004). They observed the outcome of premature luteinization which was defined as a progesteroneoestradiol ratio > 1 on the day of hCG administration.…”
Section: The Effects Of Hyperstimulation On Progesterone and Oestrogementioning
confidence: 99%
“…Group A consisted of patients whose P:E 2 ratio was 1 while Group B comprised patients with premature luteinization whose P:E 2 ratio was >1. The primary outcome measure in this study by Ozcakir et al (2004) was oocyte quality, fertilization rate and clinical pregnancy rate, which were all adversely affected by premature luteinization defined as P:E 2 ratio >1. Indeed, the pregnancy outcome of the present study could have been affected by the dominance of progesterone (P:E 2 >1) which was observed at 5.5 and 6.5 days of pregnancy in the hyperstimulated animal.…”
Section: The Effects Of Hyperstimulation On Progesterone and Oestrogementioning
confidence: 99%